Case Report: Benefits of a NSCLC Patient With EGFR A289G/F287_G288insHA cis Mutations From Immunotherapy in Combination With Antiangiogenesis and Chemotherapy and Sequential Treatment of EGFR-TKI - Zhang, He; Dong, Weiwei; Zhao, Huixia; Hu, Yanyan; You, Xia; Sun, Tingting; Xiao, Wenhua (Frontiers in Oncology, 2022)
We presented a 67-year-old non-smoking female lung adenocarcinoma patient with novel EGFR A289G/F287_G288insHA cis mutations who responded positively to sintilimab combined with regorafenib and albumin paclitaxel, and sequential treatment of icotinib. Gene mutations in patients were detected by next-generation sequencing (NGS) technology, and changes in gene mutations before and after treatments were observed by ctDNA monitoring. We observed the efficacy of the patient through chest computed tomography (CT) imaging and carcinoembryonic antigen (CEA) level and found that the patient benefited from immunotherapy in combination with anti-angiogenesis and chemotherapy for more than one year, CEA levels initially fell sharply and then rebounded during the treatment period. After changing to EGFR-TKI therapy, the CEA level of the patient also decreased sharply at the initial stage of treatment, but also rebounded and increased at the later stage of treatment. The patient was tested for genetic mutations after four months of sequential EGFR-TKI therapy and was found to have lost all previous EGFR mutations, which may be the cause of resistance to targeted drugs icotinib. We believe that our findings have enriched the EGFR mutation spectrum in NSCLC and highlighted the possible choice for patients harboring this mutation by immunotherapy combined with chemotherapy and anti-vascular therapy, and EGFR-TKI targeted therapy.